1999
DOI: 10.1097/00006123-199905000-00042
|View full text |Cite
|
Sign up to set email alerts
|

Chiari I Malformation Redefined: Clinical and Radiographic Findings for 364 Symptomatic Patients

Abstract: These data support accumulating evidence that CMI is a disorder of the para-axial mesoderm that is characterized by underdevelopment of the posterior cranial fossa and overcrowding of the normally developed hindbrain. Tonsillar herniation of less than 5 mm does not exclude the diagnosis. Clinical manifestations of CMI seem to be related to cerebrospinal fluid disturbances (which are responsible for headaches, pseudotumor-like episodes, endolymphatic hydrops, syringomyelia, and hydrocephalus) and direct compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
991
16
24

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,149 publications
(1,085 citation statements)
references
References 88 publications
54
991
16
24
Order By: Relevance
“…In our view, these two conditions – although each with its typical clinical and radiological characteristics (Friedman et al., 2013; Milhorat et al., 1999) – are both often characterized by some degree of reduced ICC as recently addressed (Frič & Eide, 2016). A particular aspect of these two conditions is that they are often present during early adulthood, that is, in much younger age than, for example, a typical case of iNPH.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In our view, these two conditions – although each with its typical clinical and radiological characteristics (Friedman et al., 2013; Milhorat et al., 1999) – are both often characterized by some degree of reduced ICC as recently addressed (Frič & Eide, 2016). A particular aspect of these two conditions is that they are often present during early adulthood, that is, in much younger age than, for example, a typical case of iNPH.…”
Section: Discussionmentioning
confidence: 80%
“…Chiari malformation type 1 (CMI), characterized by idiopathic caudal ectopy of cerebellar tonsils into foramen magnum (Milhorat et al., 1999), and idiopathic intracranial hypertension (IIH) (Friedman, Liu, & Digre, 2013) are traditionally considered to be two distinct clinical entities, although some common clinical, radiological, and pathophysiological features have been noticed (Bejjani, 2003; Frič & Eide, 2016). In particular, disturbed cerebrospinal fluid circulation (CSF) resulting in reduced intracranial compliance (ICC) has been demonstrated as a characteristic feature of both CMI and IIH (Eide & Kerty, 2011; Frič & Eide, 2015, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the symptoms reported by fibromyalgia patients are identical to those reported by patients diagnosed with two well defined neurological disorders: Chiari 1 malformation or cervical myelopathy due to spinal stenosis (spondylotic cervical myelopathy) [1,13,29]. We previously reported the radiological and neurological findings in non-randomly selected patients with fibromyalgia, documenting the presence of cervical myelopathy and cervical spinal cord compression in a cohort of 270 patients [17].…”
Section: Introductionmentioning
confidence: 87%
“…In his another study, 46% (88/190) of basilar invagination (BI) cases had AAD. In a series of 364 patients with symptomatic CMI, Milhorat et al [7] reported (BI) in 12%, atlas assimilation in 5.2%, and the Klippel-Feil anomaly in 4.9%. Such disparity has probably several reasons, such as different including criteria, surgeon's clinical experience and the use of more accurate preoperative examinations (CT and MRI).…”
Section: History Diagnostic Differential Diagnosis Epidemiologymentioning
confidence: 95%